Effect of charge status on the ion transport and antimicrobial activity of synthetic channels - Xin, Pengyang; Zhao, Lingyu; Mao, Linlin; Xu, Linqi; Hou, Shuaimin; Kong, Huiyuan; Fang, Haodong; Zhu, Haofeng; Jiang, Tao; Chen, Chang-Po (Chemical communications (Cambridge, England), 2020)
A class of unimolecular channels formed by pillararene-gramicidin hybrid molecules are presented. The charge status of the peptide domain in these channels has a significant impact on their ion transport and antimicrobial activity. These channels exhibited different membrane-association abilities between microbial cells and mammalian cells. One of the channels displayed a higher antimicrobial activity towards S. aureus (IC 50 = 0.55 μM) and negligible hemolytic toxicity, showing potential to serve as a systemic antibiotic. The charge status of channels formed by pillararene-gramicidin hybrid molecules has a significant impact on their trans-membrane transport properties, membrane-association abilities and antimicrobial activities.